ESTIMATiON OF IMMUNOBIOLOGICAL EFFICIENCY OF YAKS SPLEEN AUTOLYSATES ON THE MODEL WiTH AZATHIOPRINE IMMUNOSUPPRESSION - S. D. Zhamsaranova (Acta Biomedica Scientifica, 2012)
The article on the immunodeficiency model describes the influence of autolysates isolated from yaks spleen on the performance of cellular and. humoral immune response of experimental animals (mice). Neurotropic activity of these funds was estimated. Found, that thymic growth stimulate activity correlates with immunomodulatory and. neurotropic.